2017
DOI: 10.1186/s13018-017-0536-9
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin protects ischemic spinal cord injury from cell death and cytotoxicity through decreasing oxidative stress: in vitro primary cultured rat spinal cord model under oxygen and glucose deprivation-reoxygenation conditions

Abstract: BackgroundIschemia and the following reperfusion damage are critical mechanisms of spinal cord injury. Statins have been reported to decrease ischemia–reperfusion injury in many organs including the spinal cord. Anti-oxidative effect is one of the main protective mechanisms of statin against neuronal death and cytotoxicity. We hypothesized that statins’ anti-oxidative property would yield neuroprotective effects on spinal cord ischemia–reperfusion injuryMethodsPrimary cultured spinal cord motor neurons were is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 71 publications
0
26
0
Order By: Relevance
“…The data from this study provide new insights into the neuroprotective mechanisms of Sim. Previous clinical studies revealed that Sim has the potential to decrease the risk of PD by lowering oxidative stress [12,13], and it can also affect the suppressive potential of pathological alpha-Syn by lowering cholesterol levels [14]. The fact that Sim can cross the blood-brain barrier as well as the considerable evidence supporting the beneficial effects of Sim on the central nervous system make Sim one of the more promising drugs for treating neurodegenerative diseases, including stroke [15,16] and PD [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…The data from this study provide new insights into the neuroprotective mechanisms of Sim. Previous clinical studies revealed that Sim has the potential to decrease the risk of PD by lowering oxidative stress [12,13], and it can also affect the suppressive potential of pathological alpha-Syn by lowering cholesterol levels [14]. The fact that Sim can cross the blood-brain barrier as well as the considerable evidence supporting the beneficial effects of Sim on the central nervous system make Sim one of the more promising drugs for treating neurodegenerative diseases, including stroke [15,16] and PD [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that the functional recovery after SCI is possible (Badner and Siddiqui, 2017). However, it is difficult for NSCs to survive because of the oxidative stress environment after SCI (Sohn et al, 2017). Therefore, reducing oxidative stress injury is a vital process for NSCs to treat SCI.…”
Section: Introductionmentioning
confidence: 97%
“…Neural stem cells (NSCs) are one of the main type of stem cells. However, it is difficult for NSCs to survive because of the oxidative stress environment after SCI (Sohn et al, 2017). This finding suggests that the functional recovery after SCI is possible (Badner and Siddiqui, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the neurons in the CNS contain low levels of antioxidant enzymes [6]. Therefore, the neurons in the CNS are vulnerable to oxidative damage due to the low antioxidant ability and limited scope for up-regulation when the oxidative stress is enhanced [6]. The above descriptions indicate that oxidative stress is a promising therapeutic target for SCI treatments [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the cell membranes of the CNS, there are a great amount of lipids which are easily vulnerable to free radical. Moreover, the neurons in the CNS contain low levels of antioxidant enzymes [6]. Therefore, the neurons in the CNS are vulnerable to oxidative damage due to the low antioxidant ability and limited scope for up-regulation when the oxidative stress is enhanced [6].…”
Section: Introductionmentioning
confidence: 99%